2020
DOI: 10.1186/s12974-019-1662-6
|View full text |Cite
|
Sign up to set email alerts
|

Clemastine improves hypomyelination in rats with hypoxic–ischemic brain injury by reducing microglia-derived IL-1β via P38 signaling pathway

Abstract: Background: Microglia activation is associated with the development of hypoxic-ischemic brain injury (HIBI). Neuroinflammation suppression might be a suitable therapeutic target in hypoxic oligodendrocyte injury. This study aims to determine whether clemastine can improve hypomyelination by suppressing the activated microglia and promoting the maturation of oligodendrocyte progenitor cells (OPCs) in HIBI. Methods: A bilateral common carotid artery occlusion (BCCAO) rat model that received continuous intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Double immunofluorescence staining has shown that NLRP3 and IL-1β expression levels which are localized in the astroglia activated after ischemia-hypoxia. Our previous research found that HH1R is associated with neuroinflammation [4]. The results showed that HH1R exists in the astrocytes and the expression levels of IL-1β and NLRP3 were decreased by clemastine (H1 receptor antagonist), but the expression of HH1R was unaffected and localized in the astrocytes.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Double immunofluorescence staining has shown that NLRP3 and IL-1β expression levels which are localized in the astroglia activated after ischemia-hypoxia. Our previous research found that HH1R is associated with neuroinflammation [4]. The results showed that HH1R exists in the astrocytes and the expression levels of IL-1β and NLRP3 were decreased by clemastine (H1 receptor antagonist), but the expression of HH1R was unaffected and localized in the astrocytes.…”
Section: Discussionmentioning
confidence: 89%
“…Cardiac arrest can cause severe neurological damage that can result in a long-term unconscious state, and hypoxic-ischemic brain injury (HIBI) is the main cause of this poor prognosis [1]. The role of white matter injury in HIBI has attracted more attention, axonal hypomyelination is the pathological hallmark of HIBI [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the effect of SIS3 and LPS on inflammatory response in microglia, SIS3 (2 μl in 6-well plates or 1 μl in 24-well plates) or vehicle (DMSO) was added to the primary microglial cell cultures after enriched microglia were cultured for 1 day [ 38 ]. The final concentration of SIS3 was 10 μM.…”
Section: Methodsmentioning
confidence: 99%